Surgical treatment of complicated duodenal ulcers with different variants of their localization - Maksymchuk, D.; Mamchych, V.; Maksymchuk, V. (Journal of Education, Health and Sport, 2021)
Purpose: To analyze and highlight the most effective methods of surgical treatment of complicated duodenal ulcer (DU) depending on its location. Material and methods. 86 patients underwent surgery for complicated combined pyloroduodenal ulcers. All patients with signs of gastrointestinal bleeding and perforation were examined according to clinical protocols. Patients were operated on by various surgical techniques depending on the location of DU. Further the analysis of different methods of surgical treatment of the pathology under study at its various localizations was carried out. Results. It has been established that in complicated combined pyloroduodenal ulcers with localization in the pyloric canal antrumectomy is the method of priority. If duodenum ulcer is complicated by bleeding, excision with pyloroplasty is the method of priority. Suture ulceration with pyloroplasty can be considered as an alternative method of treatment. It has been verified that in complicated duodenal ulcers, exteriorization and suturing of the ulcer have the lowest efficiency. The most frequently used method of duodenal ulcers of any localization treatment was excision of the ulcer with pyloroplasty. 6 (41.8 ± 0.053%).patients had been operated on by this method. In the second place in terms of universality was ulcer’s suturing with pyloroplasty - 22 patients or (25.5 ± 0.047%). The third was the method of exteriorization and suturing of ulcers, which accounted for 10 patients (11.6 ± 0.034%).